Global warming advances the flowering of plane tree in Malaga (southern Spain) - Picornell Rodríguez, Antonio; Ruiz-Mata, Rocío; Gálvez-Montañez, Enrique de; Recio, Marta; Trigo-Pérez, María del Mar (My University, 2022)
Temperature has been identified as one of the most influent meteorological variable in bud development and pollen release in many arboreal taxa. Consequently, global warming is affecting the flowering phenology of many species. These changes have special relevance in the case of ornamental trees that produce highly allergenic pollen grains such as Platanus orientalis, given that variations in the temporality of its Main Pollen Season (MPS) can affect the sensitive people living in cities. The aim of this study is to detect whether or not there is any significant trend in the main parameters of production and temporality of airborne Platanus pollen in Malaga, as well as to identify the possible causes. Daily airborne pollen concentrations of Platanus were analysed for the period 1992-2021 in Malaga (southern Spain). Trends were calculated for both pollen and meteorological parameters. The thermal requirements of Platanus flowering were analysed applying three different models for chilling (Utah Model, Chilling Hours and Chill Portions), as well as the Growing Degree Hours for forcing. The relevant periods for chilling and forcing accumulation were defined according to Partial Least Squares (PLS) regression analyses. There was a significant advance in the start of the MPS of Platanus pollen (2.5 days/decade) caused by a temperature increase during the period prior to flowering. The global warming is increasing the forcing accumulation during January and February, so the forcing requirements of Platanus flowering are reached earlier and the phenophase advances. In line with these findings, the relevant dates for the chilling and forcing accumulations have advanced up to one month since 1992 according to the PLS analysis. Global warming has advanced the period of favourable temperatures for the forcing requirements of Platanus, so they are reached earlier and the flowering period advances.
Keywords: Clima - Cambios; Calentamiento global; Aerobiología; Polen; Cambio climático; plátano de sombra